A Characterisation of the Centre for Mathematics Education (Centro de Educacao Matematica - CEM), 1984-1997, as a Community of Practice for the Professional Development of Mathematics Teachers - Silva, Heloisa da [UNESP] (Unesp-dept Mathematica, 2010)
This paper presents some results of a study on the Centre for Mathematics Education (Centro de Educacao Matematica, CEM), a group of mathematics educators from the city of Sao Paulo-SP (Brazil), active mainly during the years 1984 to 1997. To establish a position on the process of identity constitution of CEM, we bring forth the method of Oral History and theories of identity. In this essay, an exercise in constituting the identity of CEM from the characterisation of this community's publications within its practice, we assume that the processes of identity constitution do not refer to what CEM is or was, but rather to a set of possibilities for apprehending it on the basis of strategies and initiatives set in given historical conditions and times. We make explicit three aspects that are present as their practice is converted into a source of coherence (mutual commitment, joint enterprise and shared repertoire), which allow one to reveal actions and production in the history of mathematics teacher education in the metropolitan region of Sao Paulo.
Keywords: CEM; Communities of Practice; Identity; Mathematics Teacher Education; Oral History